LRRK2 knockdown in zebrafish causes developmental defects, neuronal loss, and synuclein aggregation. Issue 8 (5th June 2016) - Prabhudesai, Shubhangi; Bensabeur, Fatima Zahra; Abdullah, Rashed; Basak, Indranil; Baez, Solange; Alves, Guido; Holtzman, Nathalia G.; Larsen, Jan Petter; Møller, Simon Geir
Abstract : Although mutations in the leucine‐rich repeat kinase 2 (LRRK2) gene are the most common cause of genetic Parkinson's disease, their function is largely unknown. LRRK2 is pleiotropic in nature, shown to be involved in neurodegeneration and in more peripheral processes, including kidney functions, in rats and mice. Recent studies in zebrafish have shown conflicting evidence that removal of the LRRK2 WD40 domain may or may not affect dopaminergic neurons and/or locomotion. This study shows that ∼50% LRRK2 knockdown in zebrafish causes not only neuronal loss but also developmental perturbations such as axis curvature defects, ocular abnormalities, and edema in the eyes, lens, and otic vesicles. We further show that LRRK2 knockdown results in significant neuronal loss, including a reduction of dopaminergic neurons. Immunofluorescence demonstrates that endogenous LRRK2 is expressed in the lens, brain, heart, spinal cord, and kidney (pronephros), which mirror the LRRK2 morphant phenotypes observed. LRRK2 knockdown results further in the concomitant upregulation of β‐synuclein, PARK13, and SOD1 and causes β‐synuclein aggregation in the diencephalon, midbrain, hindbrain, and postoptic commissure. LRRK2 knockdown causes mislocalization of the Na + /K + ATPase protein in the pronephric ducts, suggesting that the edema might be linked to renal malfunction and that LRRK2 might be associated with pronephric duct epithelial cell differentiation. Combined, our study shows that LRRK2 has multifaceted roles in zebrafish and that zebrafish represent a complementary model to further our understanding of this central protein. © 2016 Wiley Periodicals, Inc. Abstract : Downregulation of LRRK2 in zebrafish leads to a spectrum of developmental defects, neuronal loss, synuclein aggregation, and kidney abnormalities. Combined this study highlights the multifaceted roles played by LRRK2.